Revitalizing Quranic and Fiqh Education: The Endeavor of An-Najah Ihya’ As-Sunnah Foundation - Muhammad Sapii Harahap; Taufik Hidayat; Fian Triadi; Wafiq Azizah Muslim; Arradhau br Sipayung; Raihanah Adilah; Salwa Wudy Halia; Nunzairina Nunzairina (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community devotion program is as follows: 1) improve the ability to read the Qur'an and memorize Surah Al-Kahfi verses 1-7, 2) teach theory and practice in the implementation of prayer, as well as 3) provide the theories and introductions about mahram to pupils at the middle school level. The method used in community service at the An-Najah Foundation is Community-Based Research (CBR), a collaboration between the community and higher education institutions, with an action-oriented approach and application of service learning to support social movements to create social justice. The results of this activity in the first cycle show that most students still have difficulties understanding and following the activities carried out because the materials taught are still new to them. However, after the second cycle, the results show that: 1) average students can read the Quran and memorize Surah Al-Kahfi paragraphs 1-7, 2) average students understand the theory and practice of prayer, and 3) average students have an understanding of the theories and knowledge of Mahram.